Hubungan Komitmen Organisasi dan Budaya Organisasi dengan Organizational Citizenship Behavior di Sekolah Santo Nicholas Medan - Cindy Yohannes; Sjahril Effendy; Dedi Sahputra (Mahesa Research Center, 2022)
The aim of this research is to determine the correlation between organizational commitment and organizational culture with Organizational Citizenship Behavior at the Santo Nicholas School Medan. The hypotheses propose that there is a positive and significant correlation between organizational commitment and organizational culture with Organizational Citizenship Behavior on educators and education staff at the Santo Nicholas School Medan. The population in this research are 40 people. The sampling technique is total sampling. Data analysis is using multiple regression analysis. Research results are: 1. There is a significant correlation between organizational commitment and Organizational Citizenship Behavior. This is indicated by the coefficient value of 0.554 with the value of sig. 0.000 < 0.05 and Ha statement is accepted with correlation is enough. 2. There is a significant correlation between organizational culture and Organizational Citizenship Behavior. This is indicated by the coefficient value of 0.535 with the value of sig. 0.000 < 0.05 and Ha statement is accepted with correlation is enough. 3. There is a significant correlation between organizational commitment and organizational culture with Organizational Citizenship Behavior. This is indicated by the value of coefficient R = 0.628 with a value of sig. 0.000 < 0.05 and the Ha statement is accepted with correlation is strong. The total effective contribution of organizational commitment and organizational culture with Organizational Citizenship Behavior is 36.7% and it stated to be low.